Potability Classification of Ground Waters In Arid Zone Of Western Rajasthan - Bhandari, L M; Bhargava, T N; Purohit, A D; Gupta, I C (Annals of Arid Zone, 2016)
About 900 samples of ground waters from the four districts of Jodhpur, Jaisalmer, Barmer and Bikaner, falling in the arid-zone of western Rajasthan, have been classified in five classes on the basis of total dissolved solids, chlorides, total hardness and sulphates, and in three classes with respect to pH. Class I (good) and II (satisfactory) waters. confirm to permissive and excessive limits as per international standards devised by World Health Organisation. Class III (less satisfactory) type of waters are generally used in this region for drinking purposes satisfactorily due to scarcity of good to satisfactory potable water as far as total dissolved solids, chlorides and total hardness is concerned. Class IV (unsatisfactory) waters are also found to be in very rare use for drinking purposes in this region but their utilisation is doubtful as far as health hazard is. concerned. Class V (unpotable) waters require. definite Improvement in their quality.